144k views
15 votes
4x^2−4x+10 and 2x^2+5x-82x^2+5x−8.

User JayDi
by
4.9k points

2 Answers

9 votes

2(2x^2-2x+5) and 2(40x^2-5x+4)

Explanation:

User TimHayes
by
6.0k points
10 votes

Answer:

4x^2−4x+10 = 2(2x^2−2x+5)

2x^2+5x-82x^2+5x−8 = 2(−40x^2+5x−4)

Explanation:

4x^2−4x+10

Factor 4x^2−4x+10

4x^2−4x+10

=2(2x^2−2x+5)

2x^2+5x-82x^2+5x−8

Factor 2x^2+5x−82x^2+5x−8

−80x^2+10x−8

=2(−40x^2+5x−4)

User Mateus Zitelli
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.